The effect of Electronic Learning on Learning Short Service Skills and Forehand Shot in Badminton Players U15 - Ali, Ahmed Obaid; Remadan, Ali Jehad (Journal of Physical Education, 2021)
The research aimed at identifying the effect of electronic learning on short serve and forehand shot learning in badminton players U15. The researchers used electronic learning using pictures and videos distributed on (24) teaching units with (4) sessions per week. They used the experimental method on (16) badminton players under 15. Skill tests were applied on the subjects and each test included (12) attempts and only the best (10) were recorded and (5) marks were awarded for each attempt making a total of (50) marks. The data was collected and treated using proper statistical operations to conclude significant differences between pre and post-tests in learning some fundamental skills in badminton for players U15 in favor of post-tests.